1. The problem statement, all variables and given/known data f(x) = (1-x3)(2+x4)(3-x5)(4+x6)(5-x7)(6+x8)...(2n+1-x2n+3) Find f ' (1). 2. Relevant equations 3. The attempt at a solution f (1) = 0 because of the first term. Also the pattern is that terms with odd numbers have a subtraction sign and terms with even numbers have an addition sign. I used logarithmic differentiation ("a" & "b" denote the terms of the original function in order to avoid rewriting all that): ln y = ln a + ln b ... y' * (1/y) = (1/a) + (1/b)... y' = [(1/a) + (1/b)] * [y] y'(1) = [(1/a) + (1/b)] * [y(1) Since we already know y(1) = 0, y'(1) also equals 0. Is this correct? Any help is much appreciated. Edited: I just noticed that after differentiating, my first term would be [1/(1-x3)] and plugging 1 to x would give a fraction where 0 is the denominator. I guess that makes my solution incorrect?